Effect of Digital Economy on Rural Revitalization of Hainan Free Trade Port - Wenbo Lyu; Hao Su (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
This study comprehensively explores the impact of the digital economy on rural revitalization in Hainan Free Trade Port. It aims to analyze the current state of digital economy development and its contributions to economic growth, employment opportunities, and improvement of social services in Hainan’s rural areas. Economic data, digital development indicators, and rural revitalization-related data were collected, and statistical analysis methods were employed to evaluate the effects. The results underscore the significant role of the digital economy in promoting rural revitalization in Hainan, highlighting the potential for agricultural modernization, financial service improvement, talent training, income growth, and governance efficiency.